2022
DOI: 10.1186/s12879-022-07560-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of convalescent plasma for severe COVID-19: a randomized, single blinded, parallel, controlled clinical study

Abstract: Background Convalescent plasma (CP) has been widely used to treat COVID-19 and is under study. However, the variability in the current clinical trials has averted its wide use in the current pandemic. We aimed to evaluate the safety and efficacy of CP in severe coronavirus disease 2019 (COVID-19) in the early stages of the disease. Methods A randomized controlled clinical study was conducted on 101 patients admitted to the hospital with confirmed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Endpoint of mortality varied among studies. Thirteen trials examined 28-day mortality [ 16 21 , 26 , 29 , 32 , 33 , 37 , 38 , 40 ], six trials examined 30-day mortality [ 22 , 23 , 31 , 36 , 39 , 41 ], three trials examined 60-day mortality [ 25 , 28 , 34 ] and a single trial examined 90-day mortality [ 24 ]. Three trials broadly reported in-hospital overall mortality [ 27 , 30 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endpoint of mortality varied among studies. Thirteen trials examined 28-day mortality [ 16 21 , 26 , 29 , 32 , 33 , 37 , 38 , 40 ], six trials examined 30-day mortality [ 22 , 23 , 31 , 36 , 39 , 41 ], three trials examined 60-day mortality [ 25 , 28 , 34 ] and a single trial examined 90-day mortality [ 24 ]. Three trials broadly reported in-hospital overall mortality [ 27 , 30 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias assessment for individual trials is shown in Online Resource 2 and overall risk of bias in included trials is shown in Online Resource 3. The majority of included studies (22/26) were qualified as high-quality [ 16 – 19 , 26 , 28 34 , 37 41 ], fulfilling all five criteria of the RoB 2 Tool [ 11 ]. One or more criteria of the RoB 2 Tool [ 11 ] were either unclearly reported or completely missing in four studies [ 20 , 27 , 35 , 36 ], which were regarded as low-quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the enrolment of 101 patients with confirmed COVID-19 a randomized, single blinded, parallel, controlled study was conducted to evaluate the clinical benefits of CPT in severe COVID-19 cases [155] . The data suggested that there is increase in the nAb titre after 4 day of CPT.…”
Section: Advantages Over Other Therapeutic Regimes and Vaccinationmentioning
confidence: 99%